Insider Trading in the Swiss Stock Market - Andreas Zingg; Sebastian Lang; Daniela Wyttenbach (Swiss Journal of Economics and Statistics, 2007)
Many studies on insider trading are based on data of the U.S. market and conclude that insiders can earn abnormal profits. This paper examines for the Swiss stock market whether insiders can earn abnormal profits and whether outsiders can make abnormal profits by mimicking the transactions of insiders. We find significant abnormal returns for insider trading, as well as some evidence for profitable mimicking strategies. We can reject the strong form Efficient Market Hypothesis for the Swiss stock market. However, with regard to the semi-strong form Efficienct Market Hypothesis, it remains unclear whether it is true for the Swiss stock market.
Keywords: G14; 330; Insider trading; event study; management transactions; efficient market hypothesis